Patient preferences for disease-modifying drugs in multiple sclerosis therapy: a choice-based conjoint analysis - Utz, Kathrin S.; Hoog, Jana; Wentrup, Andreas; Berg, Sebastian; Laemmer, Alexandra; Jainsch, Britta; Waschbisch, Anne; Lee, De-Hyung; Linker, Ralf; Schenk, Thomas (Therapeutic Advances in Neurological Disorders, 2014)
With an increasing number of disease-modifying treatments (DMTs) for multiple sclerosis (MS), patient preferences will gain importance in the decision-making process. We assessed patients' implicit preferences for oral versus parenteral DMTs and identified factors influencing patients' treatment preference.Patients with relapsing-remitting MS (n = 156) completed a questionnaire assessing treatment preferences, whereby they had to decide between pairs of hypothetical treatment scenarios. Based on this questionnaire a choice-based conjoint analysis was conducted.Treatment frequency and route of administration showed a stronger influence on patient preference compared with frequency of mild side effects. The latter attribute was more important for treatment-naïve patients compared with DMT-experienced patients. The higher the Extended Disability Status Scale score, the more likely pills, and the less likely fewer side effects were preferred. Pills were preferred over injections by 93% of patients, when treatment frequency and frequency of side effects were held constant. However, preference switched to injections when pills had to be taken three times daily and injections only once per week. Injections were also preferred when pills were associated with frequent side effects.Our results suggest that route of administration and treatment frequency play an important role in the patients' preference for a given DMT.
EVALuna2:22318